Characterization of flax fabric reinforced nano-clay geopolymer composites - Assaedi, H.; Shaikh, Faiz; Low, It Meng (2016)
Geopolymer composites reinforced with flax fabrics (FF) and nanoclay platelets are synthesised and studied in terms of physical and mechanical properties. X-Ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscope (SEM) techniques are used for phase and microstructure characterisation. The nanoclay platelets are added to reinforce the geopolymer matrices at 1.0%, 2.0%, and 3.0% by weight. It is found that 2.0 wt.% nanoclay enhances the density, decreases the porosity and subsequently improves the flexural strength and toughness. The microstructural analysis results indicate that the nanoclay behaves not only as a filler to improve the microstructure of the binder, but also as an activator to support the geopolymeric reaction producing higher content of geopolymer gel. This enhances the adhesion between geopolymer matrix and flax fibres, which improves the mechanical properties of the geopolymer nanocomposites reinforced with flax fabrics.